Total hospitalizations after peripheral arterial revascularization in the VOYAGER trial. (3rd October 2022) - Szarek, M; Debus, E S; Nehler, M R; Anand, S S; Patel, M R; Haskell, L P; Muehlhofer, E S; Berkowitz, S D; Bauersachs, R M; Bonaca, M P
Abstract: Background: In the VOYAGER PAD trial, rivaroxaban reduced first and total (first and subsequent) occurrences of major adverse limb and cardiovascular events in patients with peripheral artery disease (PAD) after lower extremity revascularization (LER), but also increased incident bleeding. Purpose: Assessment of disease burden by the onset of a particular set of events does not necessarily capture all consequences of a disease process that negatively impact patients' quality of life, motivating the adoption of more patient-centered outcomes. The present analysis of VOYAGER PAD describes the total incidence and duration of hospitalizations reported during the study as a broader measure of total disease burden and net benefit of rivaroxaban therapy. Methods: Patients were randomized 1:1 to rivaroxaban 2.5 mg twice daily plus aspirin (n=3286) or aspirin alone (n=3278). Investigators documented the primary reason and duration for each hospitalization occurring after randomization. Total hospitalization rates were estimated by events per 100 patient-years. Treatment group comparisons on total hospitalizations as a time-to-event outcome were by marginal proportional hazards models with death as a competing terminal event, while days in hospital were compared by zero-inflated Poisson regression. All analyses were intention-to-treat. Results: A total of 7156 hospitalizations (3265 first, 3891 subsequent) occurred during a median 2.5 years of follow-up, with nearly 40% being hospitalizations for PAD and a small fraction attributed to bleeding events (Figure 1). The rivaroxaban rate was lower for PAD hospitalizations and higher for bleeding event hospitalizations, with more hospitalizations prevented than caused (Table 1). Mean days in hospital among patients hospitalized at least once was significantly lower in the rivaroxaban group for any reason, for PAD, and for bleeding, so that total days in hospital was numerically lower for rivaroxaban. Conclusion: Patients with PAD undergoing LER have a high rate of subsequent hospitalizations after an index procedure, driven by re-hospitalizations for PAD. Rivaroxaban decreased both the incidence and duration of PAD hospitalizations. While rivaroxaban increased incident hospitalizations due to bleeding, the mean durations of these hospitalizations were lower relative to placebo, leading to fewer total days in hospital for bleeding (1252 vs. 1531 total days). These findings may be useful for clinicians and patients weighing the risks and benefits of rivaroxaban in PAD after revascularization. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): BayerJanssen